2020
DOI: 10.1186/s11671-020-03415-9
|View full text |Cite
|
Sign up to set email alerts
|

F-actin Regulates Osteoblastic Differentiation of Mesenchymal Stem Cells on TiO2 Nanotubes Through MKL1 and YAP/TAZ

Abstract: Titanium and titanium alloys are widely used in orthopedic implants. Modifying the nanotopography provides a new strategy to improve osseointegration of titanium substrates. Filamentous actin (F-actin) polymerization, as a mechanical loading structure, is generally considered to be involved in cell migration, endocytosis, cell division, and cell shape maintenance. Whether F-actin is involved and how it functions in nanotube-induced osteogenic differentiation of mesenchymal stem cells (MSCs) remain to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 65 publications
4
25
0
Order By: Relevance
“…Generally, on the one hand, the increase of RhoA will promote the expression of ROCK2, trigger the assembly of actin, promote the conversion from G-actin e to F-actin in polymer state, increase the polymerization level of actin and increase the area of cytoskeleton, which is conducive to the osteogenic differentiation and inhibit adipogenic differentiation of BMSCs. Our study is consistent with the conclusions of Tong [37], The increase of cytoskeleton F-actin promotes osteogenic differentiation. On the other hand, the combination of ROCK2 and Phactr1 reduces the free Phactr1.…”
Section: Discussionsupporting
confidence: 93%
“…Generally, on the one hand, the increase of RhoA will promote the expression of ROCK2, trigger the assembly of actin, promote the conversion from G-actin e to F-actin in polymer state, increase the polymerization level of actin and increase the area of cytoskeleton, which is conducive to the osteogenic differentiation and inhibit adipogenic differentiation of BMSCs. Our study is consistent with the conclusions of Tong [37], The increase of cytoskeleton F-actin promotes osteogenic differentiation. On the other hand, the combination of ROCK2 and Phactr1 reduces the free Phactr1.…”
Section: Discussionsupporting
confidence: 93%
“…YAP signaling is one of the more studied and complex pathways involved in osteogenic differentiation. It has been reported that F-actin polymerization enhances the expression of RhoA and transcription factor YAP/TAZ, which promotes the osteogenic differentiation of mesenchymal stem cells [52]. In addition, through the response to different ECM stiffness, Yap and TAZ move in and out of the nucleus under the control of MT1-MMP, where YAP/TAZ can be activated on the hard matrix to make the cells differentiate into osteoblasts [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…On a microgrooved bearing surface partially mimicking the physiological reticulated microenvironment, mouse BM-derived MSCs showed a twofold to threefold increase in cell proliferation and expressed higher levels of pluripotency-related markers versus a standard 2D culture [66]. Within a certain diameter range (74-148 nm), the ability of TiO2 nanotubes to promote the osteogenic differentiation of MSCs strengthened with the increase of nanosize [67]. Micro/nano hierarchical structures generated by different nanotopographies (nanoneedle, nanosheet, and nanorod) and micropatterns of different sizes (4 µm, 12 µm, and 36 µm) gave rise to significant differences in the osteogenic differentiation potential of hBMSCs and the angiogenesis of human umbilical vein endothelial cells (HUVECs) through macrophage immunomodulation [68].…”
Section: Niche Geometrymentioning
confidence: 99%